Ethnomathematics study in calendar system of Baduy tribe - Andika Arisetyawan; Supriadi Supriadi (Universitas negeri Yogyakarta, 2020)
The aim of this research is to study ethnomathematics in the calendar system of the baduy tribe. The study of ethnomathematics in our research used ethnography methods. We found a unique pattern in baduy calendar that the first day in the previous month + 2 days after the first day of the previous month equals to the first day in the next month, in which, it is the reason why baduy people who have no mathematical knowledge from the formal school can predict, for an example, the first day in the next months.